MANAGEMENT OF PROCESSES IN FOOD PRODUCTION - Mamajonova Sarvinozxon Odiljon qizi; Shoymatova Xolida Qudrat qizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abctract Efficient management of production processes in the food industry is critical for ensuring product quality, safety, and economic efficiency. The thesis discusses methods for process control, technological integration, and personnel management within modern food manufacturing. Key innovations, including automation and IoT technologies, are explored, alongside Lean management principles for operational improvement.